Investigating Effects of Bilingualism on Syntactic Processing: Testing Structural Sensitivity Theory. Issue 2 (6th February 2022) - Siu, Tik‐Sze Carrey; Ho, Suk‐Han Connie
Abstract: The present study compared Chinese‐English bilinguals and English monolinguals within three age groups to examine whether bilinguals have an advantage in syntactic processing. Participants were tested on morphosyntactic awareness, word‐order awareness, artificial syntax learning, and general cognitive abilities. Bilinguals within the three age groups performed better than their monolingual peers in acquiring a novel syntax and in processing morphosyntax specific to English. The bilingual adults also outperformed their monolingual peers in processing language‐specific word order. Overall, the findings give credence to the structural sensitivity theory in accounting for bilingual syntactic processing. A bilingual advantage in language processing appears not confined to knowledge of and strategies specific to the additional language but constitutes a more abstract representation of underlying linguistic structure. Bilingual effects are also qualified by cross‐language differences in linguistic features, age, and the amount of bilingual experience. Abstract :